Paranoid Park - Sant, Gus Van.; Momsen, Taylor; Gabe Nevins; Jake Miller; Lauren McKinney; Daniel Lui (Ifc France USA, 2007)
An unsolved murder at Portland's infamous Paranoid Park brings detectives to a local high school, propelling a young skater into a moral dilemma where he must deal with the consequences of his own actions. As director of My Own Private Idaho, Good Will Hunting, To Die For and Elephant, Gus Van Sant has created some of the most memorable stories about youth ever committed to film. New York Press says Paranoid Park boasts "the coolest pop score since Pulp Fiction " and the film was shot by the acclaimed cinematographer Christopher Doyle (In the Mood for Love, The Quiet American). Paranoid Park also features a cast of hot newcomers including Gabe Nevins and "Gossip Girl's" Taylor Momsen.
Language(s): English, Turkish Subtitle(s): Turkish
Keywords: Drama